Global emergency, local action: safeguarding Pakistan from Mpox - Hasana, Uswa; Munir, Wahhaj; Khan, Adil (Journal of the Pakistan Medical Association, 2025)
Madam, Monkeypox (Mpox) is a zoonotic viral disease that the World Health Organization declared a public health emergency of international concern he following a surge in Africa and spread to neighbouring countries. Given the recent global impact of COVID-19 and some imported cases of Mpox in Pakistan, local action is crucial to prevent it from escalating into a national crisis. Mpox can spread between people through close contact, infected animals and contaminated materials, causing a painful rash, enlarged lymph nodes and fever. So far there are two known types (clades) of Mpox. Clade 1 is associated with the recent rise in cases with a higher risk of serious outcomes as compared to Clade 2. Pakistan’s healthcare system is already weak and it has its own challenges. Managing routine acute and chronic illnesses is different from handling an outbreak of contagious disease, which requires specialized expertise and specific protocols. According to the National Institutes of Health, a total of one death and 11 cases of Mpox have been reported in Pakistan since April, 2023. Pakistan is not isolated by any means and shares a border with four countries. Additionally, it has a fair share of travelling from many countries both developed and undeveloped. So, bracing for a rapid response might save the country from a disaster (1). Pakistan continues to face problems regarding Polio eradication and in the past was hit by COVID19. The last pandemic exposed the flaws in our healthcare system. As the virus spread initially, delays in implementing the testing, diagnosis and contact tracing lead to uncontrolled expansion of the affected virus infected population (2). Other problems included misinformation about vaccines, hesitancy for treatment, low community engagement and no social media usage in the rural population. This highlights that timely identification and a swift response are crucial for managing Mpox. Authorities should improve lab testing capacity, set up health assessments at entry points of the country and enhance disease surveillance in order to prevent Mpox outbreak. Clear communication from reliable resources is essential to dispel misinformation and reassure the public. Additionally, it is crucial to ensure that healthcare providers are informed about the latest treatment guidelines and to gather the necessary resources. Maintaining public health safety and preventing extensive transmission needs community-wide shared awareness (3). —Continue